Working memory and fluid intelligence as predictors of work engagement—Testing preliminary models. Issue 4 (20th December 2018) - Kulikowski, Konrad; Orzechowski, Jarosław
Summary: This study aimed to investigate the relationships between working memory capacity, fluid intelligence (Gf), and work engagement within the framework of the job demands–resources theory. Multioccupational employees ( N  = 175 in Study 1 and N  = 383 in Study 2) completed sets of Gf, complex span, and n ‐back tests, along with job resources and work engagement surveys. Structural equation modeling with latent variables and bootstrapping procedures revealed that complex span was indirectly positively related to work engagement via job resources, and n ‐back was indirectly positively related to work engagement via job complexity. Moreover, the one common factor g composed of Gf, n ‐back, and complex span was positively indirectly related to work engagement via job resources and job complexity. These results highlight that the cognitive capacities of employees should be given greater consideration as cognitive personal resources in models aimed at accounting for employee work engagement.